Metaethics after Moore - Horgan, Terry, 1948-; Timmons, Mark, 1951- (Oxford : Clarendon, 2010)
Metaethics is concerned to answer second-order non-moral questions about the semantics, metaphysics, and epistemology of moral thought and discourse and is often traced to G.E. Moore work. These essays represent the most up to date work in the field, after and in some cases directly inspired by Moore.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Moore, G. E. -- 1873-1958.; Ethics